Learning Materials Design Pattern Numbers Context Making Kemplang in Class IX - Yayan Eryandi; Somakim Somakim; Yusuf Hartono (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2016)
This study aims to clarify the role of making kemplang can help students understand the concept of number patterns, and generate Learning Trajectory. The methodology used in this research is the design of the research by the research subject class IX students of SMP Negeri 2 South Indralaya, Ogan Ilir, South Sumatra. Researchers designing learning activities that sensing, drafting kemplang class simulated using circular paper prepared by the researcher. Exploration proportional situations using everyday life issues are close to students' lives, such as creating kemplang can make students more interested in learning mathematics and easily understand the math problems are given. Collecting data in this study using video, observation, written tests, documentation and records during the activity. The results of this study indicate that context kemplang and paper-making circles as a model really helps students to understand the concept of a pattern of numbers.Keywords: pattern numbers, manufacture Kemplang, PMRI, design researchÂ DOI: http://dx.doi.org/10.22342/jme.7.2.3535.101-108